Membangun Karakter Mahasiswa Melalui Pelatihan ESQ Guna Meningkatkan Kompetensi Mahasiswa Untag Surabaya - Sri Budi Kasiyati, Sri Budi Kasiyati; Budiarti, Endah Budiarti (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2016)
Symptoms of dishonesty among students and the community, which marked the modeled mass assignments and exams, plagiarism cases of scientific work at several universities, indiscipline in the lecture, and corruption increased. Indicator character of the nation, especially students who began to decline becomes an important issue to study, to overcome the problems of the characters needed models that synergize all intelligence training, not only intellectual but also emotionalÂ and spiritual intelligence. The ESQ training models in an effort to build positive character of the student so that the student is not getting the moral decline. Through training, in the long run will result in increased student competence, as a potential future leader of the nation. Human Resources is able to compete, adapt, intelligent and moral, culture of corruption so lost. The population in this research is student of the faculty of economic in 2012 in Untag Surabaya.with the total number of 600 student.From the test result, analsysis of Smart PLS, random sampling method by software SmartPls 2.0,on 30 respondents, Â the study states that the ESQ training is the right model to build student character FE UNTAG Surabaya force in 2012 and build the character of students is the right model for enhancing student competence UNTAG Surabaya. ESQ training but do not directly improve the competence of students, through build character first. Key words: ESQ training, build character, competence